Srebp‐1 Interacts with c‐Myc to Enhance Somatic Cell Reprogramming. (29th September 2015) - Wu, Yi; Chen, Keshi; Liu, Xiyin; Huang, Lili; Zhao, Danyun; Li, Linpeng; Gao, Mi; Pei, Duanqing; Wang, Chenguang; Liu, Xingguo
Abstract : Somatic cell reprogramming is accompanied by changes in lipid metabolism. While attempting to dissect the molecular mechanisms of the lipid metabolic switch during reprogramming, we found that overexpression of sterol regulatory element binding protein‐1 (Srebp‐1), a transcriptional factor required for lipid homeostasis, enhances reprogramming efficiency, while knockdown or pharmaceutical inhibition of Srebp‐1 is inhibitory. Srebp‐1 overexpression blocks the formation of partially reprogrammed cells, and functions in the early phase of reprogramming. Furthermore, Srebp‐1 functions in nucleus and depends on its transcriptional activity but not its ability to bind the E‐box motif and regulation of canonical targets. Mechanistically, Srebp‐1 interacts with c‐Myc, facilitates its binding to downstream pluripotent targets, strengthens the function of c‐Myc in enhancing other Yamanaka factors' binding, and thereby promotes the expression of pluripotent genes. These results elucidate a novel role for Srebp‐1 in somatic cell reprogramming and provide insights into understanding the metabolic switch during reprogramming. Stem Cells 2016;34:83–92